(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2023)
The aim of this article is to compare two literary works (Drive Your Plough Over the Bones of the Dead by Olga Tokarczuk and The Sand of Saraswati by Risto Isomäki), which are part of the current of ecocritical studies. It is also important to bring out the similarities and differences in the view of the problem of human degradation of the natural environment, taken at the micro and macro level, in seemingly distant texts.